Extraction-Free, Direct Determination of Caffeine in Microliter Volumes of Beverages by Thermal Desorption-Gas Chromatography Mass Spectrometry - Xianglu Peng; Melanie Brown; Paul Bowdler; Kevin C. Honeychurch (International Journal of Analytical Chemistry)
An extraction-free method requiring microliter (μL) volumes has been developed for the determination of caffeine in beverages. Using a pyrolysis-gas chromatography mass spectrometry system, the conditions required for the direct thermal desorption-gas chromatography mass spectrometry (TD-GC/MS) determination of caffeine were optimised. A 5 μL aliquot was introduced to the thermal desorption unit, dried, and thermally desorbed to the GC/MS. The response was linear over the range 10 to 500 μg/mL (R2 = 0.996). The theoretical limit of detection (3 σ) was 0.456 μg/mL. No interferences were recorded from endogenous beverage components or from commonly occurring drugs, such as nicotine, ibuprofen, and paracetamol. Replicate caffeine determinations on fortified latte style white coffee and Pepsi Max® gave mean recoveries of 93.4% (%CV = 4.1%) and 95.0% (%CV = 0.98%), respectively. Good agreement was also obtained with the stated values of caffeine for an energy drink and for Coca-Cola®. These data suggest that the method holds promise for the determination of caffeine in such samples.